F-C Tutorial App: Active Learning Approach via Mobile Application Technology to Develop Student Intrapersonal Skills - Mohd Fairuz Bachok; Ainamardia Nazaruddin; Zulhafizal Othman; Zadariana Jamil@ Othman (International Journal of Asian Education, 2021)
Mobile application technology has been widely used in various fields, including education, because it is software in mobile phones owned by anyone. Besides, it easy to use anywhere and anytime. Therefore, by applying the app's merits, the Fast and Correct Tutorial App (F-C Tutorial App) is developed using this technology as a platform. The F-C Tutorial App is a weekly tutorial whereby every weekend of the lecture weeks, students can download a few questions via the app, and then the answers that had been calculated need to be filled up in the app. A survey was conducted on the target group, and the survey questions were divided into three sections: the respondent background, the agreement of F-C Tutorial App can enhance student intrapersonal skills, and the F-C Tutorial agreement App is a user-friendly tool. The group of lecturers who develop this app believes that ongoing training that can easily access and accompanied by competition for rewards is an active learning approach that can motivate students to develop their cognitive and affective skills. Besides, the rules that need to be followed to ensure the F-C Tutorial App can be easier to use and positively impact.